2004
DOI: 10.1596/1813-9450-3299
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Selectivity of Foreign Aid, 1984–2002

Abstract: We examine the allocation of foreign aid by 41 donor agencies, bilateral and multilateral. Our policy selectivity index measures the extent to which a donor's assistance is targeted to countries with sound institutions and policies, controlling for per capita income and population. The poverty selectivity index analogously looks at how well a donor's assistance is targeted to poor countries, controlling for institutional and policy environment as measured by a World Bank index. Our main finding is that the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 22 publications
8
189
1
5
Order By: Relevance
“…Interestingly, however, even in this stringent and conservative research design there is still evidence in Table 4 that like-minded donors pursue a needs-based aid allocation strategy (more aid for economic infrastructure/production sectors goes to poorer countries) and a 21 Consistent with this finding, Dollar and Levin (2006) report negative coefficients on the export variable for three donors among the largest five (Germany, the United Kingdom, and the United States). 22 The reason is that the marginal effects are dependent on the fixed effects which are conditioned out of the estimations.…”
Section: Second-stage Results: Donor Groups and Aid Sectorsmentioning
confidence: 94%
“…Interestingly, however, even in this stringent and conservative research design there is still evidence in Table 4 that like-minded donors pursue a needs-based aid allocation strategy (more aid for economic infrastructure/production sectors goes to poorer countries) and a 21 Consistent with this finding, Dollar and Levin (2006) report negative coefficients on the export variable for three donors among the largest five (Germany, the United Kingdom, and the United States). 22 The reason is that the marginal effects are dependent on the fixed effects which are conditioned out of the estimations.…”
Section: Second-stage Results: Donor Groups and Aid Sectorsmentioning
confidence: 94%
“…In the existing literature, such variables reflecting the governments' general political stance as well as their economic policies have frequently been shown to influence MDB lending (Burnside & Dollar, 2000;Dollar & Levin, 2004;Dreher et al, 2009aDreher et al, , 2009bKilby, 2006, Thacker, 1999. We also include IMF lending as an alternative source of funding, and the countries' population as a simple scaling factor.…”
Section: Discussionmentioning
confidence: 99%
“…We do not apply an economic 24 Dollar and Levin (2004) have shown that bilateral and multilateral donors did not target countries with good institutions from 1984-1989. In fact, they can only find support for good institutions targeting occurring after 1995, thus excluding the bulk of our observations.…”
Section: Control Variablesmentioning
confidence: 99%